Scaling justice India's Supreme Court, anti-terror laws, and social rights - Shankar, Shylashri, 1967- (New Delhi ; Oxford : Oxford University Press, 2009)
What explains the choices that India's Supreme Court justices make? Shankar addresses this question by combining a textured qualitative analysis of the constitutional and legal framework, landmark rulings, and dissenting opinions, with a statistical multivariate analysis of cases dealing with civil liberties and social rights. She argues that judges are 'embedded negotiators' who craft judgments to avoid conflict with the political wings, while also remaining mindful of their role as safe keepers of the rights of citizens.
Description based on print version record.
Includes bibliographical references and index.
Keywords: India. -- Supreme Court; Preventive detention -- India; Terrorism -- India -- Prevention; Social rights -- India